Roman stamped bricks from the Tussla-collection in the Hungarian National Museum - Linda Dobosi; Tamás Szabadváry (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae)
The so-called Tussla-collection of the Hungarian National Museum is a substantial collection of Roman artefacts collected by Mr. and Mrs. Tivadar Tussla during the early 1880s in the northern half of the legionary fortress in Brigetio. The original material consisted of about 2.500 objects that were partly donated to the Museum during the 1880s or formed the private collection of Mrs. Tussla and entered the Museum after her death in 1961. Both the Tussla couple and the collection had a troubled and eventful fate which led to the loss of some of the material. In this paper, the extant pieces of the ceramic building material are discussed. From the original almost 400 objects 100 could be found in the brick collection of the Hungarian National Museum, most of them stamped. The material is very diverse, both in terms of brick types and stamp types. The different kinds of ceramic building material catalogued include two antefixes, five terracotta water pipes, four tubuli, 21 round suspensura bricks, 32 rectangular lateres, 30 tegulae and 5 imbrices. Almost half of the objects are whole, and their original size could be measured, showing a larger than expected variety. Stamps occurred on tegulae, imbrices, lateres, round bricks and even on a tubulus. About two thirds of the brick stamps (59 out of 86) were those of the legio I Adiutrix, the garrison of Brigetio for three centuries. The other 27 stamps belonged to 10 other manufacturers: the legio XI Claudia (4), legio XXX Ulpia Victrix (2), cohors VII Breucorum (6), classis Flavia Histrica (1), Quadriburgium (3), Frigeridus dux (1), Terentius dux (1), Lupicinus tribunus (6), Terentianus tribunus (1) and Corta Vicen (2). The Tussla-collection enhances greatly our knowledge about the legionary fortress of Brigetio and forms a solid supplement to the ongoing excavations.